NILAI-NILAI PENDIDIKAN ISLAM DALAM KEGIATAN SHALAWATAN GROUP "CINTA RASUL" DI DUSUN LUMBANG PENYENGAT - Elsa Safitri; Eka Kurniati; Nur Asika; Siti Hardiyanti; Siti Nurdini (Jurnal Ilmu Pendidikan dan Sosial, 2022)
Shalawat reading is done as a form of love and longing for the prophet Muhammad SAW. By reading shalawat, it is hoped that the prophet will intercede on the last day. In shalawat there are poems that are very meaningful and have educational value. Shalawatan activities will usually be led by a prayer group and witnessed by the public, thus indirectly inviting the community to read prayers together. Lumbang Penyengat Hamlet has a prayer group with the name Cita Rasul. With the Cinta Rasul prayer group, it is hoped that it can invite the people of Lumbang Penyengat Hamlet to always pray as a form of love and longing for Rasulullah SAW. The value of aqidah education means believing, believing and as a soul force that can control and bind the human heart. Always pray, try to take care of the heart, and improve self-quality. Because not only chanting sholawat to the Prophet Muhammad SAW, the community also learns the law of recitation, and inserts fiqh knowledge before the prayer begins. Sholawat activities also have moral education value. Moral education is the soul of Islamic education and to achieve a good and perfect character is the goal of education. The third is Social education Humans are social creatures, creatures who cannot live alone, creatures who always need the help of others. This prayer activity also builds ties of friendship, mutual responsibility, care for each other, protect each other, help fellow members. education